Influences of HLH-2 stability on anchor cell fate specification during Caenorhabditis elegans gonadogenesis. Issue 4 (3rd February 2022) - Benavidez, Justin M; Kim, Jee Hun; Greenwald, Iva
Abstract: The Caenorhabditis elegans E protein ortholog HLH-2 is required for the specification and function of the anchor cell, a unique, terminally differentiated somatic gonad cell that organizes uterine and vulval development. Initially, 4 cells—2 α cells and their sisters, the β cells—have the potential to be the sole anchor cell. The β cells rapidly lose anchor cell potential and invariably become ventral uterine precursor cells, while the 2 α cells interact via LIN-12/Notch to resolve which will be the anchor cell and which will become another ventral uterine precursor cell. HLH-2 protein stability is dynamically regulated in cells with anchor cell potential; initially present in all 4 cells, HLH-2 is degraded in presumptive ventral uterine precursor cells while remaining stable in the anchor cell. Here, we demonstrate that stability of HLH-2 protein is regulated by the activity of lin-12/ Notch in both α and β cells. Our analysis provides evidence that activation of LIN-12 promotes degradation of HLH-2 as part of a negative feedback loop during the anchor cell/ventral uterine precursor cell decision by the α cells, and that absence of lin-12 activity in β cells increases HLH-2 stability and may account for their propensity to adopt the anchor cell fate in a lin-12 null background. We also performed an RNA interference screen of 232 ubiquitin-related genes and identified 7 genes that contribute to HLH-2 degradation in ventral uterine precursor cells; however, stabilizing HLH-2 by depleting ubiquitin ligases in a lin-12(+) background does not result in supernumerary anchor cells, suggesting that LIN-12 activation does not oppose hlh-2 activity solely by causing HLH-2 protein degradation. Finally, we provide evidence for lin-12 -independent transcriptional regulation of hlh-2 in β cells that correlates with known differences in POP-1/TCF levels and anchor cell potential between α and β cells. Together, our results indicate that hlh-2 activity is regulated at multiple levels to restrict the anchor cell fate to a single cell.